2019
DOI: 10.4252/wjsc.v11.i6.347
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences between mesenchymal stem/progenitor cells derived from various human tissues

Abstract: BACKGROUND Mesenchymal stromal/stem cells (MSCs) constitute a promising tool in regenerative medicine and can be isolated from different human tissues. However, their biological properties are still not fully characterized. Whereas MSCs from different tissue exhibit many common characteristics, their biological activity and some markers are different and depend on their tissue of origin. Understanding the factors that underlie MSC biology should constitute important points for consideration for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 75 publications
9
113
0
4
Order By: Relevance
“…In the healthy skeletal muscle, a balance is maintained between these myogenic progenitors and the FAPs, and the FAPs are believed to aid in muscle regeneration [28,29]. Kozlowska et al showed that MSCs from the healthy skeletal muscles have the limited adipogenic potential [30], and Marinkovic et al showed that seeding purified skeletal muscle stem cells and FAPs in co-culture at a 1: 1 ratio inhibits lipid droplet formation even under adipogenic conditions [31]. Aging can cause changes in skeletal muscle progenitor cells (e.g., decreased numbers, senescence).…”
Section: Discussionmentioning
confidence: 99%
“…In the healthy skeletal muscle, a balance is maintained between these myogenic progenitors and the FAPs, and the FAPs are believed to aid in muscle regeneration [28,29]. Kozlowska et al showed that MSCs from the healthy skeletal muscles have the limited adipogenic potential [30], and Marinkovic et al showed that seeding purified skeletal muscle stem cells and FAPs in co-culture at a 1: 1 ratio inhibits lipid droplet formation even under adipogenic conditions [31]. Aging can cause changes in skeletal muscle progenitor cells (e.g., decreased numbers, senescence).…”
Section: Discussionmentioning
confidence: 99%
“…Even though MSCs harvested from various tissue sources meet all three criteria set for MSCs (see above), an increasing number of comprehensive flow cytometry and immunocytochemistry analysis reveal that MSCs exhibit profound differences in their transcriptome profile [50] and protein expression when isolated from different sources [51,52]. Moreover, the origin of MSCs has an influence on the maintenance of expression of specific markers during the cell culture period [52]. The proliferation rate of MSCs of fetal origin is higher compared to cells isolated from adult tissues [51].…”
Section: Sox1mentioning
confidence: 99%
“…For autologous cell transplantation, from all tissue sources of MSC adipose tissue is one of the most accessible. MSCs themselves possess high self-renewal potential, differentiation capacity, and secretory properties, thus, making them useful for clinical application [8]. According to the world's largest clinical trials database run by the US National Library of Medicine at the National Institutes of Health, five clinical studies are currently ongoing to test the potential of atMSCs in the treatment of chronic wounds associated with diabetic foot syndrome or venous stasis ulcer (https://clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%